Study on the toxicological effect of synthetic marijuana, it’s compounds and derivatives in society - Barbosa, Aldryelle de Souza; Lima, Salatiel Henrique Pereira de; Andrade , Bianca Sheila Conceição de; Salles, Sammuel Welton Eloy; Lima, Liliane Bezerra de (Seven Editora, 2023)
In Brazil, there was a more than significant increase in the use and commercialization of synthetic marijuana over an average of 5 years. Also known as “K2”, “K9” or “Spice”, it’s a chemical substance that simulates the effects of Cannabis Sativa, but is produced in the laboratory and may contain different chemical compounds. The reason for it’s increase has been mainly due to its relatively low price and the lack of traditional drug tests, making it attractive to vulnerable groups such as the poor, people below the poverty line, children and adolescents who see the opportunity to enter the world of drugs. In this way, the work seeks to elucidate the toxicology of synthetic marijuana and its dangers for human use, focusing on possible compounds and their consequences. DOI:https://doi.org/10.56238/sevened2023.004-021